ЛУВСАННОРОВШАРАВЫН “САЙН ГАЛАВЫН МЯНГАН БУРХАНЫ МӨРГӨЛ ТАХИЛЫН ЕРӨӨЛ” ХЭМЭЭХ ЗОХИОЛЫН УРАН САЙХНЫ ОНЦЛОГ - Д.Бүрнээ (Acta Mongolica, 2011)
Luvsannorovsharav was one of the famous Mongolian authors who wrote their works in Tibetan. His work entitled ‘*bskal bzang sangs rgyas stong phrag gi phyag mchod smon lam dang bcas pa bsod nams kyi myu gu ‘phel bar byed pa’i bdud rtsi’i char chen zhes bya ba bzhugs”’ is included in the first volume of his work. As mentioned in the colophon of this work, it was written in the year of female ox or in 1757 year in the monastery of Bilig Delgerekh. The main feature of this work is that it has a lot of metaphors and epithets. Also one interesting legend is included in this work. This legend’s name is Story of Good Magadha, which was cited many times by Tibetan and Mongolian authors. - The comparison of this legend with fragments of the same legend written by other authors shows us the Luvsannorovsharav’s creative attitude to his work.